Delayed Release HPMC Capsules for Efficient Delivery of Cholecalciferol Solid Dispersion - Rawat, Neha; Khan, Nabab; Singh, Shashank K.; Patil, Umesh K.; Baldi, Ashish (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: The deficiency of Vitamin D is associated with an increased risk of various diseases and deficiency of this Vitamin is recognized in individuals all over the world. Therefore, the intake of Vitamin D has become essential. Objectives: Cholecalciferol (Vitamin D3) is a poorly soluble molecule and it is very sensitive to degradation under environmental factors such as light, temperature, and oxygen. Its stability is also affected adversely under acidic conditions. Therefore, solid dispersion-based formulation for cholecalciferol was developed and encapsulated in delayed release hydroxypropylmethyl cellulose (HPMC) capsules. Materials and Methods: Cholecalciferol solid dispersion was developed and characterized by Fourier transform–infra red spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and X-ray diffraction analysis. The effect of various concentrations of cholecalciferol formulations on the viability of Caco-2 cells was determined by using MTT assay. Dissolution profile and stability study of the developed product was also evaluated. Results: The results demonstrated improved solubility of cholecalciferol in solid dispersion-based formulation. The drug content of solid dispersions was in the order of 91±2.3% and various studies showed the amorphous form of cholecalciferol in the solid dispersion. The cell viability assay in Caco-2 cells demonstrated that the surfactant used in the solid dispersion formulation of cholecalciferol had no adverse effect on intestinal cells. Further, dissolution profile of HPMC capsule encapsulated solid dispersion showed improved dissolution of cholecalciferol. Moreover, the stability study indicated no significant changes in the cholecalciferol content in the developed formulation under storage at experimental conditions. Conclusion: The solid dispersion-based formulation of cholecalciferol exhibited improved solubility and found to be compatible with Caco-2 cells. The delayed release HPMC capsule encapsulated solid dispersion of cholecalciferol (DRHCap-SD) showed improved dissolution and acceptable stability profile and this represent a potential delivery system for oral administration of cholecalciferol.
Keywords: Solid dispersion; Cholecalciferol; HPMC capsule; Caco-2 cells; Oral delivery; Dissolution